2017
DOI: 10.1089/ten.tea.2016.0508
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Exosomes for Therapeutic Angiogenesis in Peripheral Ischemia

Abstract: Peripheral ischemia as a result of occlusive vascular disease is a widespread problem in patients older than the age of 65. Angiogenic therapies that can induce microvascular growth have great potential for providing a long-lasting solution for patients with ischemia and would provide an appealing alternative to surgical and percutaneous interventions. However, many angiogenic therapies have seen poor efficacy in clinical trials, suggesting that patients with long-term peripheral ischemia have considerable the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 106 publications
1
20
0
Order By: Relevance
“…Coincidentally, EVs derived from monocytes containing miR-27a also play promoting role in the polarization of M2 macrophages [17]. Moreover, miR-27a that promotes proliferation and migration of glioblastoma cells is abundant in glioblastoma-EVs [18]. These works further support our statement that miR-27a-3p contained in glioblastoma-EVs could polarize M2 macrophage.…”
Section: Discussionsupporting
confidence: 79%
“…Coincidentally, EVs derived from monocytes containing miR-27a also play promoting role in the polarization of M2 macrophages [17]. Moreover, miR-27a that promotes proliferation and migration of glioblastoma cells is abundant in glioblastoma-EVs [18]. These works further support our statement that miR-27a-3p contained in glioblastoma-EVs could polarize M2 macrophage.…”
Section: Discussionsupporting
confidence: 79%
“…Exosomes loaded in alginate-based hydrogels might be considered in this area for preserving the exosomes in the wound site and acting as an extracellular matrix. Monteforte et al (201) reported the use of alginate hydrogels loaded with glioma-derived exosomes to enhance revascularization in peripheral ischemia. Alginate beads with exosomes induced angiogenesis in vivo showing their potential therapeutic effect for isquimia.…”
Section: Alginate As Immobilization Matrix For Cardiac Cellsmentioning
confidence: 99%
“…The pro-angiogenic effect of GBM MVs was associated with several angiogenic proteins, such as vascular endothelial growth factor (VEGF), angiogenin, interleukin-6 (IL-6), IL-8, tissue factor (TF), tissue inhibitor of metalloproteinase-1 (TIMP-1) and TIMP-2 [33,34,40,42,[105][106][107][108]. For instance, GSC-EVs loaded with VEGF initiate angiogenesis in brain endothelial cells, thus, supporting GSCs perivascular niche.…”
Section: Mtor-dependent Gsc-derived Evs Promote Gbm Angiogenesismentioning
confidence: 99%
“…Likewise, EVs-delivered miR26a promotes angiogenesis of HBMECs by up-regulating VEGF, through the activation of the PI3K/Akt pathway, via PTEN inhibition [118]. Similarly, exosomal miR-221 from GSCs markedly enhances endothelial tube formation and proliferation [107]. Again, exosome-mediated transfer of long non-coding RNA POU3F3 (linc-POU3F3) from GSCs to brain ECs can promote angiogenesis.…”
Section: Mtor-dependent Gsc-derived Evs Promote Gbm Angiogenesismentioning
confidence: 99%